3‐D Magnetotelluric Imaging of the Easternmost Kunlun Fault: Insights Into Strain Partitioning and the Seismotectonics of the Jiuzhaigou Ms7.0 Earthquake. Issue 5 (14th May 2020) - Sun, Xiangyu; Zhan, Yan; Unsworth, Martyn; Egbert, Gary; Zhang, Huiping; Chen, Xiaobin; Zhao, Guoze; Sun, Jianbao; Zhao, Lingqiang; Cui, Tengfa; Liu, Zhongyin; Han, Jing
Abstract: We present a three‐dimensional electrical resistivity model of the crust and upper mantle beneath the easternmost Kunlun fault (EKLf), obtained by three‐dimensional inversion of magnetotelluric (MT) data. The crust of the Songpan‐Ganzi block is characterized by high resistivity from the surface to a depth of around 20 km, and by low resistivity in the mid‐lower crust in the depth range 20–40 km. The eastern edge of the high conductivity layer is coincident with the EKLf and the Huya fault. The electrical resistivity structure provides new insights into both (1) the generation of recent M > 6 earthquakes and (2) strain partitioning on this segment of the EKLf. Our model reveals that the Huya fault is the main branch of the EKLf in the region. Together with the EKLf, the Huya fault defines the boundary between the Songpan‐Ganzi and Bikou blocks. The mid‐lower crust of the Songpan‐Ganzi block in this region has a low resistivity that likely represents a mechanically weak layer. The 2017 Jiuzhaigou Ms7.0 earthquake and other recent M > 6 earthquakes may have been controlled by the change in viscosity in the mid‐lower crust that occurs across this boundary. The high conductivity may be acting as either (1) a channel of lower crustal flow, or (2) as a weak layer that decouples the upper and lower crust. The fact that the high conductivity layer does not extend along the north side of the Sichuan Basin questions the idea that crustal flow occurs in this area. Key Points: Magnetotelluric data were used to generate a 3‐D resistivity model of the easternmost Kunlun fault The Huya fault is the main boundary fault between the Songpan‐Ganzi block and Bikou block and coincides with a change in resistivity Seismicity and strain partitioning are controlled by the change in rheology inferred from the geometry of a high conductivity layer (HCL)